PENGARUH KOMPETENSI DAN LEADER MEMBER EXCHANGE TERHADAP KINERJA MELALUI KOMITMEN ORGANISASI PADA PERSONIL DITRESKRIMUM POLDA SULTRA - Zukamdani Wisudawan Zakaria; Dedy Takdir Syaifuddin; La Ode Asfahyadin Aliddin (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2023)
The purpose of this study was to determine and analyze the effect of competence on organizational commitment of the personnel of the Ditreskrimum Polda Sultra. Leader member exchange on organizational commitment. Competence on performance. Leader member exchange on performance. Organizational commitment to performance. Competence on performance through organizational commitment mediated commitment and leader member exchange on performance mediated organizational commitment. The population in this study were 56 personnel. Data analysis in this study is SmartPLS version 3.0. The results of this study indicate that competence has a positive and significant effect on organizational commitment of the Ditreskrimum Polda Sultra personnel. This means that the better the competence, the higher the organizational commitment. Leader member exchange has a positive and significant effect on organizational commitment. This means that the better the leader member exchange, the higher the organizational commitment. Competence has a positive and significant effect on performance. This means that the better the competence , the better the performance of the personnel . Leader member exchange has a positive and significant effect on personnel performance. This means that the better the competence, the higher the organizational commitment. Organizational commitment has a positive and significant effect on personnel performance. This means that the better the organizational commitment, the better the performance of personnel. Competence has a positive and significant effect on performance mediated by organizational commitment. This means that competence will improve personnel performance through organizational commitment. Leader member exchange has a positive and significant effect on performance mediated by organizational commitment.